2018
DOI: 10.1108/ijdrbe-10-2016-0042
|View full text |Cite
|
Sign up to set email alerts
|

Municipal collaborative planning boosting climate resilience in the built environment

Abstract: Purpose A meta-study covering the past decade maps the development of Norwegian municipal planning, climate adaptation and institutional vulnerability towards climate change. This paper aims to explore the implementation of climate adaptive changes in Norwegian legal planning and building framework into municipal practice and policy instruments from 2007 to 2016. The study is planned to answer the question: what drivers ensure increased municipal efforts in their climate adaptive planning and building practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 10 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…While, the measures within the Norwegian Water Directive should be adequate to safeguard climate adaptation within Norway, at the municipal level, implementation often fails [24] and the adoption of SUDS projects has lagged behind expectation [22]. Klaussen et al (2015) found that in urban planning, climate adaptation occurs randomly, and this is typically due to longstanding, conventional routines, policies, or strategies [25].…”
Section: Climate Adaptation Within Norway: Implementation and Preceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…While, the measures within the Norwegian Water Directive should be adequate to safeguard climate adaptation within Norway, at the municipal level, implementation often fails [24] and the adoption of SUDS projects has lagged behind expectation [22]. Klaussen et al (2015) found that in urban planning, climate adaptation occurs randomly, and this is typically due to longstanding, conventional routines, policies, or strategies [25].…”
Section: Climate Adaptation Within Norway: Implementation and Preceptionmentioning
confidence: 99%
“…Klaussen et al (2015) found that in urban planning, climate adaptation occurs randomly, and this is typically due to longstanding, conventional routines, policies, or strategies [25]. Identified challenges to implementation have included: conventional attitudes to planning, resistance to change, lack of knowledge and competence, unequal access and engagement with support networks, and a short supply in the recruitment of highly qualified personnel [24]. Additional studies showed that municipalities lack the right kind of competence and expertise to succeed with climate adaptation [26,27].…”
Section: Climate Adaptation Within Norway: Implementation and Preceptionmentioning
confidence: 99%
“…The need to obtain commitment towards network participation and output among political leaders, and the task of convincing them that the network approach does help to address policy challenges, have also been highlighted by other studies (Sørensen and Torfing, 2017; Torfing et al , 2012). An evaluation of a large network consisting of the 13 biggest cities in Norway (Cities of the Future), showed that endorsement by the mayor of a municipality was pivotal to the ultimate impact of the network (Flyen et al , 2017). This is an argument for addressing the network invitation directly to the mayor.…”
Section: Analysis: Identifying Key Factors That Ensure Network Achievementsmentioning
confidence: 99%
“…In this paper, the term “multilevel network” is used to describe a network that incorporates at least two public sector authority levels within its structure. Multilevel networks have been shown to play central roles ensuring greater awareness and learning (Hanssen et al , 2013; Klaussen et al , 2015; Flyen et al , 2017), but little is known of the mechanisms operating within a network that result in specific actions.…”
Section: Introductionmentioning
confidence: 99%
“…New knowledge of risk may also emerge as part of the planning and development process of a new area or housing development; according to the Norwegian Planning and Building Act, evaluation of risk of natural hazards should be undertaken in advance of new developments. In contrast, the last few years have seen the emergence of several adaptation networks that seem to boost collaboration across scales and sectors in the government and increase competence and inspire solutions for adaptation in municipalities (Hauge et al 2018;Flyen et al 2018). Still, municipalities are struggling with proactive adaptation due to a lack of capacity, resources and knowledge of adaptation measures (Aall et al 2018).…”
Section: Introductionmentioning
confidence: 99%